New-Generation Quality and Safety Management of the Construction Industry - Xie Xianqi; Deng Liming; Xiao Mingzhao; Luo Hanbin; Fang Ruiwei (中国工程科学, 2021)
Construction is a complex human–machine–environment system, and the quality and safety management during construction faces numerous challenges. As the new-generation information technology develops, digital twin now can be used in construction to improve the quality and safety management and promote smart construction in China. Computability and controllability of the whole construction process is expected to be achieved using the digital twin technology; digital management of construction sites can be realized using advanced sensing, computing, and other technologies. In this article, we first investigate the demand for the application of digital twin into the construction quality management and analyze the research status and problems of the application. Subsequently, we propose a next-generation construction quality and safety management system that is composed of product intelligent design for construction quality and safety control, intelligent sensing and analysis of construction quality and safety status, data-driven construction quality and safety control, and construction quality management and dynamic supervision. Furthermore, we propose suggestions for the application of digital twin technology in the construction industry in China from the aspects of management, technology, as well as standards and specifications.